A study of information needs and uses of agricultural scientists working in research institutes within the Agency for Agricultural Research and Development (AARD) in Indonesia - Wiryoadipoero, Soewarto; Buenrostro, Juan Jr. C.; Vallejo, Rosa M. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1984)
The aim of this study is to identify the information needs and uses of agricultural scientists working in research institutes within the Agency for Agricultural Research and Development (AARD) in Indonesia, in relation with information services being provided by the National Library for Agricultural Sciences (NLAS) in support of their research activities. It was designed and carried out in November and December 1983.A comprehensive questionnaire was developed and distributed to 300 agricultural scientists 214 or 71 percent of whom responded.
The major findings of the study are: agricultural scientists are frequent users of the library, and they seek information mostly to keep abreast of development in their field and acquire new ideas for their work. The most preferred sources of information are the abstracting journals.
Furthermore, a greater percentage of these scientists were satisfied with the current available information services of NLAS; however, it was likewise expressed by the agricultural scientists that they could have been more productive in their research efforts if the information services in NLAS had been better than the present available services.
On the basis of the findings, it is concluded that NLAS could not as yet satisfy all the information needs of the agricultural scientists of AARD. The information services are inadequate and thus should be improved and expanded. Moreover, the quality of the library staff at NLAS stands further improvement.
The study recommends that: 1. The present NLAS collection should be improved and expanded to meet the information needs of the agricultural scientists in research institutes within AARD. An evaluation of the existing collection should be conducted with the help of these scientists. 2. Upgrade the library personnel through formal education as well as attendance in seminars or meetings related to agriculture. They should be oriented to new developments in the library field such as information awareness services, information retrieval systems, and information delivery systems.3. Users' profiles of the agricultural scientists should be compiled to know their specific information requirements.4. The Selective Dissemination of Information (SDI) should be improved by providing important and useful information to the agricultural scientists.5. Continuous research studies on the information needs and preferences of the agricultural scientists should be carried out. Extra efforts on the part of NLAS management should be made to know and identify the needs of the agricultural scientists.6. These research studies should be conducted by the library staff in order that they will become aware of the specific information requirements of the agricultural scientists.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Agriculturists -- Information services -- Indonesia; Indonesia. Ministry of Agricultural Research and Development -- Information services